How to build a virtual community: Evidence from 7 cases - Robert Tietz; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2007)
Companies are starting to recognize the need to build a virtual community. They want to achieve a brought range of goals but face different, more demanding requirements when building a virtual community than do other providers. To give companies a guideline on how to establish their own virtual community we developed a process-model by means of an explorative case-study analysis. By looking into seven processes of how companies from the German hobby and leisure-products industry have built their virtual communities we gained many insights and derived a five-step process that can be used by companies to build a virtual community.
Keywords: 650